Impact of empagliflozin add-on therapy on quality of life in patients of type 2 diabetes mellitus with hypertension: A prospective study - Imtiyaz Ahmed Najar; Shariq Rashid Masoodi; Shakeel Ahmed Mir; Moomin Hussain Bhat; Rakesh Raman Patyar; Sazal Patyar (Wolters Kluwer Medknow Publications, 2022)
Background: Diabetes has a negative impact on patient's quality of life (QoL). Comorbidities and polypharmacy further worsen their QoL. Thus, in addition to glycemic control, assessment of QoL is also gaining importance. Objective: The objective of this study was to evaluate QoL in patients of type 2 diabetes mellitus (T2DM) with hypertension after add-on empagliflozin to triple drug therapy (metformin, teneligliptin, and glimepiride). Materials and Methods: A prospective research was done on T2DM patients with hypertension, who visited a tertiary care referral institute's endocrine outpatient clinic. For 3 months, empagliflozin, 25 mg once daily, was administered as an add-on treatment with metformin, teneligliptin, and glimepiride. In addition to clinical assessment, an Urdu-translated QoL instrument for Indian diabetes patients was used to conduct QoL study. The QoL outcomes prior to empagliflozin add-on were compared with those obtained at the conclusion of the 3 months of treatment. Results: Empagliflozin as an add-on therapy significantly improved various aspects of QoL like role limitation due to physical health, physical endurance, general health, symptom botherness, financial worries, emotional/mental health, and diet satisfaction (P < 0.001). It also improved glycemic and blood pressure parameters significantly. Conclusion: QoL is an essential measure with respect to patient-centered treatment approach. Empagliflozin, as an add-on medication, improved QoL, glycemic parameters and blood pressure in T2DM patients with hypertension. It can be recommended as an add-on, but more research with a larger sample size is required.